SPECIFICS OF TRANSLATION OF MILITARY AVIATION TERMS - Rakhimov Murad Jumabaevich; Parmonov Bakhtiyor Sariboevich (Western European Studies, 2024)
This article discusses the translation of military aviation terms from English into Uzbek and Russian. The study of military terms is relevant due to the rapid development of modern science and technology. Particular attention is paid to the translation of simple and complex military terms, consideration of borrowings and the main methods of translating abbreviations.
Keywords: term; multicomponent terms; aviation terms and abbreviations